A Morphological Stylistic Analysis of Song “I Wish I Hated You” by Ariana Grande - Mutiara Romi Artika; Vina Fitriani Dalimunte; Devi Sofilla; Rahmadsyah Rangkuti (Humanitatis : Journal of Language and Literature, 2024)
In societal interactions, language plays a fundamental role, serving crucial purposes. Language activities aim to express specific intentions and objectives. This study aims to examines Ariana Grande's song "I Wish I Hated You" using a stylistic approach, focusing on morphological analysis of free and bound morphemes, including lexical, functional, derivational, and inflectional morphemes, and their relation to the song's theme. The research method used is a qualitative descriptive method. The primary data source is the lyrics of the song. The data collection process involved listening to the song, reading the lyrics, and categorizing them based on morpheme types. The research results indicate 74 lexical morphemes, 102 functional morphemes, 3 derivations, and 16 inflections in the song. Dominant morphemes are primarily free morphemes, with functional morphemes being the most prevalent type. This highlights how the selection and arrangement of dominant morphemes shape the song's overall impact and message. The research contributes to appreciate Ariana Grande's song, uncover deeper meanings, and enhance understanding of morpheme types within the lyrics.